Preparation and in-system study of SnCl2 precursor layers: towards vacuum-based synthesis of Pb-free perovskites. Issue 1 (3rd January 2018) - Félix, R.; Llobera-Vila, N.; Hartmann, C.; Klimm, C.; Hartig, M.; Wilks, R. G.; Bär, M.
Abstract : Characterization of SnCl2 thin-films, inorganic precursor to Sn-based perovskites, UHV-deposited on Mo reveals widespread chemical structure along film layer profile. Abstract : The chemical structure and topography evolution of vapor-deposited SnCl2 thin-films on Mo-coated glass substrates was studied via a combination of electron spectroscopies and scanning electron microscopy. For this purpose, a thickness series of SnCl2 thin-films was prepared using different evaporation times, revealing significant changes in the chemical environment of Sn and Cl along the layer profile and layer topography. The presence of O in the Mo-coated substrates can lead to oxidation in the SnCl2 film layers. The findings in this work show the effect that substrate conditions can exert on the chemical (and electronic) properties of the deposited material layers and that need to be taken into account for device optimization.